2004
DOI: 10.1016/j.jpdc.2003.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Incomplete k-ary n-cube and its derivatives

Abstract: Incomplete or pruned k-ary n-cube, nX3; is derived as follows. All links of dimension n À 1 are left in place and links of the remaining n À 1 dimensions are removed, except for one, which is chosen periodically from the remaining dimensions along the intact dimension n À 1: This leads to a node degree of 4 instead of the original 2n and results in regular networks that are Cayley graphs, provided that n À 1 divides k: For n ¼ 3 ðn ¼ 5Þ; the preceding restriction is not problematic, as it only requires that k … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…They also derived results relating to the diameter, the average inter-node distance and the layout of these networks. Incomplete (or pruned) k-ary n-cubes were derived by Parhami and Kwai in [34] and properties relating to symmetry, shortest paths, connectivity and Hamiltonicity were established. Certain pruned 3-dimensional tori were also studied by Xiao and Parhami in [40], and in [41] Xiao and Parhami established general algebraic constructions (based on commutative groups) to develop pruning techniques, which were used to improve known results relating to honeycomb networks and to diamond networks.…”
Section: Related Workmentioning
confidence: 99%
“…They also derived results relating to the diameter, the average inter-node distance and the layout of these networks. Incomplete (or pruned) k-ary n-cubes were derived by Parhami and Kwai in [34] and properties relating to symmetry, shortest paths, connectivity and Hamiltonicity were established. Certain pruned 3-dimensional tori were also studied by Xiao and Parhami in [40], and in [41] Xiao and Parhami established general algebraic constructions (based on commutative groups) to develop pruning techniques, which were used to improve known results relating to honeycomb networks and to diamond networks.…”
Section: Related Workmentioning
confidence: 99%
“…Let S be as above and AE ¼ CayðH; T Þ, where T ¼ fs 1 ; s qþ1 ; s À1 qþ1 g. Then, AE is known as cube-connected cycles CCC q . It is the pruned network obtained from the graph À ¼ CayðG; SÞ, which is a ðq þ 1ÞD torus [10]. Fig.…”
Section: Some Known Pruned Networkmentioning
confidence: 99%
“…Under certain conditions, when the original networks are Cayley graphs, so are the pruned versions [9], [10]. Thus, the pruned networks maintain node symmetry while benefiting from lower node degree, sparser wiring, and simpler layout.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is easily shown that a number of pruning schemes, in-cluding the one studied in [8], are equivalent to the construction above. Pruning of interconnection networks constitutes a way of obtaining variants with lower implementation cost, and greater scalability and packageability [9]. If pruning is done with care, and in a systematic fashion, many of the desirable properties of the original (unpruned) network, including (node, edge) symmetry and regularity, can be maintained while reducing both the node degree and wiring density which influence the network cost.…”
Section: Honeycomb and Other Networkmentioning
confidence: 99%